THE EFFECTIVENESS OF LOGOTHERAPY COUNSELING TO INCREASE THE MEANING OF LIFE FOR PIP RECIPIENT VOCATIONAL STUDENTS - Lia Mita Syahri; Firman; Neviyarni; Yarmis Syukur (RADJA PUBLIKA, 2023)
The government is trying to reduce poverty by providing assistance, one of which is in the field of education, the problems that occur with PIP students make this assistance not have an optimal impact. This study aims to analyze the application of counseling using logotherapy techniques to increase the meaning of life in vocational students receiving PIP. The population of this study was 93 PIP recipient students, the sample was taken using a simple random technique. Data collection uses observation, interviews and meaningful life questionnaires. This research uses a quantitative approach with a quasi-experimental design type. Data were analyzed using statistical analysis of the percentage formula to determine the state of the meaning of life in students, so that it can be seen that the condition of the meaning of life for vocational students receiving PIP has a percentage of 47, 31%, while to determine the effectiveness of using logotherapy techniques analyzed using the Wilcoxon signed rank test formula. The results showed that logotherapy counseling was effective in increasing the meaning of life for vocational students receiving PIP with an Asymp Sig value. (2-tailed) of 0.005.